1974
DOI: 10.2307/1935157
|View full text |Cite
|
Sign up to set email alerts
|

Preadult Competition between Drosophila Pavani and Drosophila Melanogaster, Drosophila Simulans, and Drosophila Willistoni

Abstract: We evaluated genetic differences between two populations of Drosophila melunoguster that differed in thermal tolerance. Adults of one tropical population (Mali) survived heat shock (39.5"C for 30 min.) at 84%. By contrast, those from a strain collected in Denmark survived at a rate of only 53 'YO. The greatest effect on variation was differences in cytoplasms, but variation in chromosomes 2 and 1 also played a role on tolerance. Heat shock proteins, however, reside on chromosome 3 and, therefore, variation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…In contrast, the interference would be the most decisive factor. These last authors remember that in the laboratory, the larvae of D. pavani Brncic inhibit the growth of other species, particularly of D. willistoni, and that facilitates the development of its own larvae (Budnik & Brncic 1974 This fact illustrates the difficulty of understanding the complex patterns found in the assemblies of Neotropical insects, and it is a sign of the stability of species in the mature assemblies. As Tidon-Sklorz & Sene (1992) affirm, the complexity of the dynamics of the tropical assemblies is a result of the interventions in the populations by factors such as ambient variation, natural selection, genetic derivation and inbreeding at different times and in different spaces.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the interference would be the most decisive factor. These last authors remember that in the laboratory, the larvae of D. pavani Brncic inhibit the growth of other species, particularly of D. willistoni, and that facilitates the development of its own larvae (Budnik & Brncic 1974 This fact illustrates the difficulty of understanding the complex patterns found in the assemblies of Neotropical insects, and it is a sign of the stability of species in the mature assemblies. As Tidon-Sklorz & Sene (1992) affirm, the complexity of the dynamics of the tropical assemblies is a result of the interventions in the populations by factors such as ambient variation, natural selection, genetic derivation and inbreeding at different times and in different spaces.…”
Section: Resultsmentioning
confidence: 99%
“…The biological basis of a conditioning of this type may be attributed, as Huang, Singh & Kojima (1971) have pointed out, either to the differential exploitation by distinct genotypes of several nutritional resources in the medium, or to the liberation by larvae of metabolic products with autotoxic effects. Recently, Brncic (1974 and have demonstrated, in several P < 0.01 NS = not significant, P/> 0.05 * = P < 0.05 ** = P < 0.01 species of Drosophila, an effect on viability of the metabolic products secreted by larvae. In the case of D. pavani, these authors found the secreted products to have an autotoxic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Interference has also been investigated in Drosophila although usually in the context of the competition between different species. These experiments provide evidence which suggests that larval metabolic products might be responsible (in part) for determining the viability of individuals of the same or different species (Sang, 1949;Budnik and Brncic, 1974). Weisbrot (1966) concluded that such medium conditioning, whether by the same or different genotypes, could result either in an improvement or a reduction in viability.…”
Section: Introductionmentioning
confidence: 93%